Ethno-STEM-Based E-Book on Colligative Properties of Solutions to Improve Students' Chemical Literacy and Sustainability Awareness - Harianto, Bibit; Pursitasari, Indarini Dwi; Heliawati, Leny; Syarpin, Syarpin (Yayasan Keluarga Guru Mandiri, 2026)
This project aims to develop and test Ethno-STEM-based e-books to enhance students’ chemical literacy and sustainability awareness regarding the colligative properties of solutions. The e-book’s development integrates coordination science with local knowledge, enabling students to understand chemical concepts in a relevant and applicable manner. The research strategy employed is RD using the ADDIE model. The e-book was approved by media and content specialists and tested on students to assess its effectiveness in improving chemical education and sustainability awareness. The level of feasibility based on media expert judgment is 89% in the